miR-1202 is a primate-specific and brain-enriched microRNA involved in major depression and antidepressant treatment - Lopez, Juan Pablo; Lim, Raymond; Cruceanu, Cristiana; Crapper, Liam; Fasano, Caroline; Labonte, Benoit; Maussion, Gilles; Yang, Jennie P; Yerko, Volodymyr; Vigneault, Erika; El Mestikawy, Salah; Mechawar, Naguib; et al. (Nature medicine, 2014)
Gustavo Turecki and colleagues report that miR-1202, a miRNA specific to primates, is decreased in individuals with depression and seems to be differentially regulated in individuals who will end up showing beneficial responses to antidepressant treatment compared to those who will not respond. Major depressive disorder (MDD) is a prevalent mood disorder that is associated with differential prefrontal brain expression patterns 1 . Treatment of MDD includes a variety of biopsychosocial approaches. In medical practice, antidepressant drugs are the most common treatment for depressive episodes, and they are among the most prescribed medications in North America 2 , 3 . Although antidepressants are clearly effective, particularly for moderate to severe depressive episodes, there is variability in how individuals respond to antidepressant treatment. Failure to respond has individual, economic and social consequences for patients and their families 4 . Several lines of evidence demonstrate that genes are regulated through the activity of microRNAs (miRNAs), which act as fine-tuners and on-off switches of gene expression 5 , 6 , 7 . Here we report on complementary studies using postmortem human brain samples, cellular assays and samples from clinical trials of patients with depression and show that miR-1202, a miRNA specific to primates and enriched in the human brain, is differentially expressed in individuals with depression. Additionally, miR-1202 regulates expression of the gene encoding metabotropic glutamate receptor-4 ( GRM4 ) and predicts antidepressant response at baseline. These results suggest that miR-1202 is associated with the pathophysiology of depression and is a potential target for new antidepressant treatments.